HUBUNGAN KEPEMIMPINAN TRANSFORMASIONAL DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PERAWAT (Studi Pada Perawat RSIA Eria Bunda Pekanbaru) - Afif Pratama; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the relations between transformational leadership andnurses’ organizational behavior citizenship (Studies on nurses of RSIA Eria Bunda Pekanbaru).This research method is descriptive and quantitative using SPSS 17 program, wherein the samples used are nurses of RSIA Eria Bunda Pekanbaru with respondents as many 76 people. For a sampling technique researchers used census method. Data collection is done through questioners and interviews.The results of the analysis is achived by using the validity test, reliability test, correlation test, t test, so it can be seen that the variables of transformational leadership has a significant relationship with organizational behavior citizenship.Keywords: transformational leadership, organizational citizenship behavior